Dari pelepah kurma ke cloud storage: evolusi metodologi preservasi teks suci dalam tradisi keilmuan islam - Suharis, M. Restu (Maliki Interdisciplinary Journal, 2026)
This study examines the evolution of Qur'anic and Hadith preservation methodology from classical to digital era, revealing how codification principles developed by classical scholars remain relevant in addressing contemporary literacy challenges. Using historical-comparative analysis and epistemological approaches, this article traces the transformation of preservation media from palm leaves, parchment, to digital databases, while maintaining rigorous verification standards. Findings indicate that the sanad-matan critique methodology developed by hadith scholars represents the precursor to modern critical historiography, while the qira'at system and Uthmanic rasm reflect sophisticated linguistic awareness. A paradox emerges when high digital accessibility creates fragmentation of scholarly authority and dissemination of unverified information. This research concludes that the intellectual legacy of codification lies not in its storage medium, but in the epistemological framework that prioritizes multiple verification, methodological transparency, and scholarly integrity. Adapting these principles in the digital ecosystem requires recontextualization without compromising established authenticity standards.